Christopher Deacy, Faith in Film: Religious Themes in Contemporary Cinema. - Kozlovic, Anton Karl (Journal for the academic study of religion, 2007)
Christopher Deacy, Faith in Film: Religious Themes in Contemporary Cinema. Ashgate, Aldershot, 2005, pp. 170, ISBN 0754651584 (hbk).